Germination response to water availability in populations of Festuca pallescens along a Patagonian rainfall gradient based on hydrotime model parameters - Lopez, Aldana Soledad (2021)
Sensitivity to water availability is a key physiological trait for grassland species located in arid and semiarid environments, where successful germination is closely related to rainfall dynamics. Festuca pallescens inhabits diverse environments along a steep precipitation gradient in North Patagonia, thus offering a suitable model for the study of germination behavior in response to water availability. By analyzing germination in nine populations using a hydrotime model approach, we aimed to find within-species variation. Seed population behavior was analyzed under different hydric conditions using hydrotime model parameters (hydrotime, mean base water potential and its standard deviation). We estimated the mean base water potential for F. pallescens (ψb(50) = − 2.79 ± 0.45 MPa), which did not differ significantly between populations. However, the hydrotime parameter (θH) varied markedly, suggesting physiological adaptation to local environments. Higher values of θH were found in populations located at the extremes of the distribution gradient, indicating that germination may be prevented or delayed in conditions that are suboptimal for the species. Since the variation in hydrotime model parameters did not follow a cline, micro-environmental cues may have the greatest influence on the physiological behavior of the species, rather than the macroscale rainfall gradient.